Mechanical Behavior of Triaxial Geogrid Used for Reinforced Soil Structures - Jun Zhang; Wen-Zhao Cao; Yan-Jun Zhou (Advances in Civil Engineering)
Geosynthetics-reinforced soil (GRS) structures have been widely used for the prevention of geological hazards. As a recently introduced product, the triaxial geogrid has been confirmed to provide improved performance due to the more stable grid structure. This paper presents an evaluation of the mechanical behavior based on a series of laboratory tests. The unconfined tensile strength of biaxial geogrid and triaxial geogrid in different loading directions relative to the orientation of ribs was investigated. Then, more than 8 pullout tests were conducted on the triaxial geogrid specimens embedded in the compacted sand. The internal displacements along the geogrid length were monitored. The results show that the triaxial geogrid has been shown to provide nearly uniform tensile strength in all loading directions as compared with the biaxial geogrid. The triaxial geogrid deformation is mainly characterized by rib bending and nodal distortion along with an inward squeeze perpendicular to the pullout direction. The interface friction between the soil and the geogrid develops in a progressive mode, and an elasto-plastic-softening characteristic is detected experimentally due to the extensibility of geogrid.